Economic valuation of the environmental services of the Coata river basin, Puno-Peru (Revista Innova Educación, 2021)
The objective of the research was to economically value the environmental services of the Coata river watershed; Likewise, determine the willingness to pay for the improvement of environmental services and identify the socio-economic variables that determine the willingness to pay. The contingent valuation method and the binomial logit econometric model were applied, with a sample of 369 households living around the basin, for this the primary source data collection technique was used and the survey on the population was used as an instrument. that resides in the basin, using the statistical packages SPSS 25.0 and Stata 16.0 for the estimation and contrast of hypotheses. It was determined that the economic value of the DAP amounts to 4.88 soles per month, thus evidencing the existence of full willingness to pay by the families that live in the vicinity of the river basin. Finally, the DAP is explained by age in 2.77%, education in 3.1%, frequency of use of the environmental service in 2.3% and distance to the river in 2.3%.
Keywords: River watershed; willingness to pay; environmental services; economic valuation